Protein adsorption steers blood contact activation on engineered cobalt chromium alloy oxide layers. (15th September 2015) - Milleret, Vincent; Buzzi, Stefano; Gehrig, Peter; Ziogas, Algirdas; Grossmann, Jonas; Schilcher, Katrin; Zinkernagel, Annelies S.; Zucker, Arik; Ehrbar, Martin
Graphical abstract: Abstract: Biomaterials upon implantation are immediately covered by blood proteins which direct the subsequent blood activation. These early events determine the following cascade of biological reactions and consequently the long-term success of implants. The ability to modulate surface properties of biomaterials is therefore of considerable clinical significance. Goal of this study was an in-depth understanding of the biological response to cobalt chromium stent alloys with engineered surface oxide layers, which showed altered body reactions in vivo . We analyzed in vitro the biological events following initial blood contact on engineered cobalt chromium surfaces featuring said oxide layers. Surface-specific blood reactions were confirmed by scanning electron microscopy and the adsorbed protein layers were characterized by mass spectrometry. This powerful proteomics tool allowed the identification and quantification of over hundred surface-adhering proteins. Proteins associated with the coagulation cascade, platelet adhesion and neutrophil function correlated with the various blood surface activations observed. Furthermore, results of pre-coated surfaces with defined fibrinogen–albumin mixtures suggest that neutrophil adhesion was controlled by fibrinogen orientation and conformation rather than quantity. This study highlights the importance of controlling the biological response in the complex protein–implant surface interactions and the potential of the surface modifications to improve the clinical performance of medical implants. Statement of Significance: The blood contact activation of CoCr alloys is determined by their surface oxide layer properties. Modifications of the oxide layer affected the total amount of adsorbed proteins and the composition of the adsorbed protein layer. Additionally fibrinogen coatings mediated the surface-dependent neutrophil adhesion in a concentration-independent manner, indicating the influence of conformation and/or orientation of the adsorbed protein. Despite the complexity of protein–implant interactions, this study highlights the importance of understanding and controlling mechanisms of protein adhesion in order to improve and steer the performance of medical implants. It shows that modification of the surface oxide layer is a very attractive strategy to directly functionalize metallic implant surfaces and optimize their blood interaction for the desired orthopedic or cardiovascular applications.